Time-resolved second-order autocorrelation function of parametric down-conversion - Horoshko, Dmitri B.; Srivastava, Shivang; Sośnicki, Filip; Mikołajczyk, Michał; Karpiński, Michał; Brecht, Benjamin; Kolobov, Mikhail I. (Physical Review A)
We study a possibility of measuring the time-resolved second-order autocorrelation function of one of two beams generated in type-II parametric down-conversion by means of temporal magnification of this beam, bringing its correlation time from the picosecond to the nanosecond scale, which can be resolved by modern photodetectors. We show that such a measurement enables one to infer directly the degree of global coherence of that beam, which is linked by a simple relation to the number of modes characterizing the entanglement between the two generated beams. We illustrate the proposed method by an example of photon pairs generated in a periodically poled potassium titanyl phosphate (KTP) crystal with a symmetric group velocity matching for various durations of the pump pulse, resulting in different numbers of modes. Our theoretical model also shows that the magnified double-heralded autocorrelation function of one beam exhibits a local maximum around zero delay time, corresponding to photon bunching at a short time scale.

Self-guided tomography of time-frequency qudits - Serino, Laura Maria; Rambach, Markus; Brecht, Benjamin; Romero, Jacquiline; Silberhorn, Christine (Quantum Science and Technology)
Abstract High-dimensional time-frequency encodings have the potential to significantly advance quantum information science; however, practical applications require precise knowledge of the encoded quantum states, which becomes increasingly challenging for larger Hilbert spaces. Self-guided tomography (SGT) has emerged as a practical and scalable technique for this purpose in the spatial domain. Here, we apply SGT to estimate time-frequency states using a multi-output quantum pulse gate. We achieve fidelities of more than 99% for 3- and 5-dimensional states without the need for calibration or post-processing. We demonstrate the robustness of SGT against statistical and environmental noise, highlighting its efficacy in the photon-starved regime typical of quantum information applications.

The Frequency‐Domain Lattice Boltzmann Method (FreqD‐LBM): A Versatile Tool to Predict the QCM Response Induced by Structured Samples - Johannsmann, Diethelm; Häusner, Paul; Langhoff, Arne; Leppin, Christian; Reviakine, Ilya; Vanoppen, Viktor (Advanced Theory and Simulations)
Abstract The quartz crystal microbalance with dissipation monitoring (QCM‐D) is routinely used to investigate structured samples. Here, a simulation technique is described, that predicts the shifts of frequency and half bandwidth, Δ f n and ΔΓ n , of a quartz resonator operating on different overtone orders, n , induced by structured samples in contact with the resonator surface in liquid. The technique, abbreviated as FreqD‐LBM, solves the Stokes equation in the frequency domain. The solution provides the complex amplitude of the area‐averaged tangential stress at the resonator surface, from which Δ f n and ΔΓ n are derived. Because the dynamical variables are complex amplitudes, the viscosity can be complex, as well. The technique naturally covers viscoelasticity. Limitations are linked to the grid resolution and to problems at large viscosity. Validation steps include viscoelastic films, rough surfaces, an oscillating cylinder in a viscous medium, and a free‐floating sphere above the resonator. Application examples are soft adsorbed particles, stiff adsorbed particles, and a large, immobile spherical cap above the resonator, which allows to study the high‐frequency properties of the material in the gap. FreqDLBM runs on an office PC and does not require expert knowledge of numerical techniques. It is accessible to an experimentalist.

Comparing the SEI Formation on Copper and Amorphous Carbon: A Study with Combined Operando Methods - Stich, Michael; Leppin, Christian; Krauss, Falk Thorsten; Valdes Landa, Jesus Eduardo; Pantenburg, Isabel; Roling, Bernhard; Bund, Andreas (Batteries)
The solid electrolyte interphase (SEI) on the anode of lithium-ion batteries (LIBs) has been studied thoroughly due to its crucial importance to the battery’s long-term performance. At the same time, most studies of the SEI apply ex situ characterization methods, which may introduce artifacts or misinterpretations as they do not investigate the SEI in its unaltered state immersed in liquid battery electrolyte. Thus, in this work, we focus on using the non-destructive combination of electrochemical quartz crystal microbalance with dissipation monitoring (EQCM-D) and impedance spectroscopy (EIS) in the same electrochemical cell. EQCM-D can not only probe the solidified products of the SEI but also allows for the monitoring of viscoelastic layers and viscosity changes of the electrolyte at the interphase during the SEI formation. EIS complements those results by providing electrochemical properties of the formed interphase. Our results highlight substantial differences in the physical and electrochemical properties between the SEI formed on copper and on amorphous carbon and show how formation parameters and the additive vinylene carbonate (VC) influence their growth. The EQCM-D results show consistently that much thicker SEIs are formed on carbon substrates in comparison to copper substrates.

Rapid Solidification of Plant Latices from Campanula glomerata Driven by a Sudden Decrease in Hydrostatic Pressure - Langhoff, Arne; Peschel, Astrid; Leppin, Christian; Kruppert, Sebastian; Speck, Thomas; Johannsmann, Diethelm (Plants)
By monitoring the solidification of droplets of plant latices with a fast quartz crystal microbalance with dissipation monitoring (QCM-D), droplets from Campanula glomerata were found to solidify much faster than droplets from Euphorbia characias and also faster than droplets from all technical latices tested. A similar conclusion was drawn from optical videos, where the plants were injured and the milky fluid was stretched (sometimes forming fibers) after the cut. Rapid solidification cannot be explained with physical drying because physical drying is transport-limited and therefore is inherently slow. It can, however, be explained with coagulation being triggered by a sudden decrease in hydrostatic pressure. A mechanism based on a pressure drop is corroborated by optical videos of both plants being injured under water. While the liquid exuded by E. characias keeps streaming away, the liquid exuded by C. glomerata quickly forms a plug even under water. Presumably, the pressure drop causes an influx of serum into the laticifers. The serum, in turn, triggers a transition from a liquid–liquid phase separated state (an LLPS state) of a resin and hardener to a single-phase state. QCM measurements, optical videos, and cryo-SEM images suggest that LLPS plays a role in the solidification of C. glomerata.

Swelling Degree of Polyelectrolyte Layers Determined by an Electrochemical Quartz Crystal Microbalance - Leppin, Christian; Pomorska, Agata; Morga, Maria; Pomastowski, Pawel; Fijałkowski, Piotr; Michna, Aneta; Johannsmann, Diethelm (Biomacromolecules)
Various polycations and polyanions were sequentially adsorbed onto the gold electrode of a quartz crystal microbalance with dissipation monitoring. The study focused on determining the adsorption kinetics, viscoelastic properties, and electroresponsivity of polyelectrolyte layers. For the first time, it was demonstrated that the structure (compact or expanded) of the layers can be determined by electroresponsivity. Viscoelastic modeling alone did not provide a conclusive answer as to whether the layers were compact or expanded. The study was further enriched by streaming potential and contact angle measurements, where polyelectrolyte multilayers were formed on mica. It was found that successive adsorption of layers led to periodic inversion of the zeta potential. Systematic differences were observed between the different top layers, which were explained by intermixing between layers. The presence or absence of interpenetration, as determined by the measurements of streaming potential and contact angles, correlated well with electroresponsivity.

A fast electrochemical quartz crystal microbalance (EQCM) evidences the presence of nanobubbles in alkaline water splitting - Leppin, Christian; Langhoff, Arne; Johannsmann, Diethelm (Physical Chemistry Chemical Physics)
Nanobubbles in water splitting are recognized by the EQCM-D. They are ubiquitous. Lifetimes are in the range of seconds.

Can diffusion degeneracies enhance complexity in chemotactic aggregation? Finite-time blow-up on spheres in a quasilinear Keller–Segel system - Winkler, Michael (Journal of the European Mathematical Society)
The Cauchy problem in \mathbb{R}^{n} for the cross-diffusion system \begin{cases}u_{t} = \nabla \cdot (D(u)\nabla u) - \nabla\cdot (u\nabla v), \\ 0 = \Delta v +u,\end{cases} is considered for n\ge 2 and under assumptions ensuring that D suitably generalizes the prototype given by D(\xi)=(\xi+1)^{-\alpha}, \quad \xi\ge 0. Under the assumption that \alpha>1 , it is shown that for any r_{\star}>0 and \delta\in (0,1) one can find radially symmetric initial data from C_{0}^{\infty}(\mathbb{R}^{n}) such that the corresponding solution blows up within some finite time, and that this explosion occurs throughout certain spheres in an appropriate sense, with any such sphere being located in the annulus \overline{B}_{r_\star+\delta}(0)\setminus B_{(1-\delta)r_\star}(0) .This is complemented by a result revealing that when \alpha<1 , any finite-mass unbounded radial solution must blow up exclusively at the spatial origin.

A switch in dimension dependence of critical blow-up exponents in a Keller-Segel system involving indirect signal production - Tao, Youshan; Winkler, Michael (Journal of Differential Equations)

A unified approach to existence theories for singular chemotaxis systems with nonlinear signal production - Tao, Youshan; Winkler, Michael (Science China Mathematics)

Rough Data in an Evolution System Generalizing 1D Thermoviscoelasticity with Temperature-Dependent Parameters - Winkler, Michael (Applied Mathematics & Optimization)
Abstract A Neumann-type initial-boundary value problem for $$\begin{aligned} \left\{ \begin{array}{l} u_{tt} = \nabla \cdot (\gamma (\Theta ) \nabla u_t) + a \nabla \cdot (\gamma (\Theta ) \nabla u) + \nabla \cdot f(\Theta ), \\ \Theta _t = D\Delta \Theta + \Gamma (\Theta ) |\nabla u_t|^2 + F(\Theta )\cdot \nabla u_t, \end{array} \right. \end{aligned}$$ u tt = ∇ · ( γ ( Θ ) ∇ u t ) + a ∇ · ( γ ( Θ ) ∇ u ) + ∇ · f ( Θ ) , Θ t = D Δ Θ + Γ ( Θ ) | ∇ u t | 2 + F ( Θ ) · ∇ u t , is considered in a smoothly bounded domain $$\Omega \subset \mathbb {R}^n$$ Ω ⊂ R n , $$n\ge 1$$ n ≥ 1 . In the case when $$n=1$$ n = 1 , $$\gamma \equiv \Gamma $$ γ ≡ Γ and $$f\equiv F$$ f ≡ F , this system coincides with the standard model for heat generation in a viscoelastic material of Kelvin-Voigt type, well-understood in situations in which $$\gamma =const$$ γ = c o n s t . Covering scenarios in which all key ingredients $$\gamma ,\Gamma ,f$$ γ , Γ , f and F may depend on the temperature $$\Theta $$ Θ here, for initial data which merely satisfy $$u_0\in W^{1,p+2}(\Omega )$$ u 0 ∈ W 1 , p + 2 ( Ω ) , $$u_{0t}\in W^{1,p}(\Omega )$$ u 0 t ∈ W 1 , p ( Ω ) and $$\Theta _0\in W^{1,p}(\Omega )$$ Θ 0 ∈ W 1 , p ( Ω ) with some $$p\ge 2$$ p ≥ 2 such that $$p>n$$ p > n , a result on local-in-time existence and uniqueness is derived in a natural framework of weak solvability.

Exactly wave-type homoclinic orbits and emergence of transient exponential growth in a super-fast diffusion equation - Hanfland, Celina; Winkler, Michael (Journal of Elliptic and Parabolic Equations)
Abstract For $$p>2$$ p > 2 , the equation $$\begin{aligned} u_t = u^p u_{xx}, \qquad x\in \mathbb {R}, \ t\in \mathbb {R}, \end{aligned}$$ u t = u p u xx , x ∈ R , t ∈ R , is shown to admit positive and spatially increasing smooth solutions on all of $$\mathbb {R}× \mathbb {R}$$ R × R which are precisely of the form of an accelerating wave for $$t<0$$ t < 0 , and of a wave slowing down for $$t>0$$ t > 0 . These solutions satisfy $$u(· ,t)→ 0$$ u ( · , t ) → 0 in $$L^∞ _{loc}(\mathbb {R})$$ L loc ∞ ( R ) as $$t→ + ∞ $$ t → + ∞ and as $$t→ -∞ $$ t → - ∞ , and exhibit a yet apparently undiscovered phenomenon of transient rapid spatial growth, in the sense that $$\begin{aligned} \lim _{x→ +∞ } x^{-1} u(x,t) \quad \text{ exists } \text{ for } \text{ all } t<0, \end{aligned}$$ lim x → + ∞ x - 1 u ( x , t ) exists for all t < 0 , that $$\begin{aligned} \lim _{x→ +∞ } x^{-\frac{2}{p}} u(x,t) \quad \text{ exists } \text{ for } \text{ all } t>0, \end{aligned}$$ lim x → + ∞ x - 2 p u ( x , t ) exists for all t > 0 , but that $$\begin{aligned} u(x,0)=K e^{α x} \qquad \text{ for } \text{ all } x\in \mathbb {R}\end{aligned}$$ u ( x , 0 ) = K e α x for all x ∈ R with some $$K>0$$ K > 0 and $$α >0$$ α > 0 .

Effects of degeneracies in taxis-driven evolution - Winkler, Michael (Mathematical Models and Methods in Applied Sciences)
Refined investigation of chemotaxis processes has revealed a significant role of degeneracies in corresponding motilities in a number of application contexts. A rapidly growing literature concerned with the analysis of resulting mathematical models has been capable of solving fundamental issues, but various problems have remained open, or even newly arisen. The goal of the paper consists in a summary of some developments in this area, and particularly in the discussion of the question how far the introduction of degeneracies may influence the behavior of solutions to chemotaxis systems.

Structural Optimization of Meta-Reinforcement Learning-based Finite-Control-Set Direct Torque Control of Permanent Magnet Synchronous Motors - Jakobeit, Darius; Peña López, Mario; Schenke, Maximilian; Haucke-Korber, Barnabas; Wallscheid, Oliver (2025 IEEE International Electric Machines & Drives Conference (IEMDC))

Reinforcement Learning-based Direct Torque Control of Externally Excited Synchronous Motors: a Proof of Concept - Haucke-Korber, Barnabas; Aung, Nyi Nyi; Schenke, Maximilian; Peña López, Mario; Jakobeit, Darius; Wallscheid, Oliver (2025 IEEE International Electric Machines & Drives Conference (IEMDC))

Reinforcement Learning Control of Three-Level Converter Permanent Magnet Synchronous Machine Drives - Peña López, Mario; Schenke, Maximilian; Jakobeit, Darius; Haucke-Korber, Barnabas; Wallscheid, Oliver (2025 IEEE International Electric Machines & Drives Conference (IEMDC))

Linear dimension of group actions - Devillers, Alice; Giudici, Michael; Hawtin, Daniel R.; Klawuhn, Lukas-André Dominik; Morgan, Luke
Two fundamental ways to represent a group are as permutations and as matrices. In this paper, we study linear representations of groups that intertwine with a permutation representation. Recently, D'Alconzo and Di Scala investigated how small the matrices in such a linear representation can be. The minimal dimension of such a representation is the linear dimension of the group action and this has applications in cryptography and cryptosystems. We develop the idea of linear dimension from an algebraic point of view by using the theory of permutation modules. We give structural results about representations of minimal dimension and investigate the implications of faithfulness, transitivity and primitivity on the linear dimension. Furthermore, we compute the linear dimension of several classes of finite primitive permutation groups. We also study wreath products, allowing us to determine the linear dimension of imprimitive group actions. Finally, we give the linear dimension of almost simple finite $2$-transitive groups, some of which may be used for further applications in cryptography. Our results also open up many new questions about linear representations of group actions.

Protest gegen Kommerzialisierung im Fußball: Theoretische Überlegungen zu Entstehung, Strukturen und Nutzen - Riedl, Lars; Meier, Heiko (FuG – Zeitschrift für Fußball und Gesellschaft)
Ausgangspunkt des Beitrags sind die wiederkehrenden Zuschauerproteste gegen die Kommerzialisierung des Fußballs und die Frage nach einer Erklärung für deren Entstehung. Gezeigt wird, dass Zuschauerproteste bereits umfassend beforscht sind, bislang allerdings keine theoretische Einordung zu ihrer Entwicklung vorgelegt wurde. Entsprechend liegt das Ziel des Beitrags darin, unter Rückgriff auf systemtheoretische Überlegungen, insbesondere auch zur Funktion des Publikums für den Fußball, und typologische Unterscheidungen, angereichert durch kulturanthropologische Betrachtungen, theoretische Erklärungen für die Ursprünge und Bedeutung von Zuschauerprotesten zu liefern. Im Anschluss hieran wird betrachtet, wie sich Zuschauerproteste in theoretische Konzepte zu Protestbewegungen einordnen lassen, um abschließend deren Nutzen für die Fußballclubs und -verbände zu bestimmen.

In Situ Investigation of the Frictional Behaviour in Friction-Spinning - Wiens, Eugen; Hijazi, Dina; Jüttner, Maik; Homberg, Werner; Kensy, Mark Dennis; Tillmann, Wolfgang (Journal of Manufacturing and Materials Processing)
Friction-spinning is an incremental thermomechanical forming process that has huge potential due to its simple yet effective mechanism of utilising friction between a rotating workpiece and a forming tool to increase the workpiece’s temperature, which reduces the required forces and increases formability during the forming process. Despite the simplicity of the process’s setup, the thermomechanical loads and high relative velocities involved, especially in the contact zone, make the application of classical methods for characterising friction inaccurate. It is therefore essential to find a way to describe the frictional behaviour under real process conditions to be able to gain a holistic understanding of the process and the effect of the adjustable parameters on the outcome, especially the temperature. To achieve this goal, an experimental setup that considers the actual process boundary conditions in forming tubes made of EN AW-6060 was used to measure in situ normal and frictional forces, in addition to process temperatures, under varying rotational speed and feed rate values.

Moderate-to-large deviation asymptotics for real eigenvalues of the elliptic Ginibre matrices - Byun, Sung-Soo; Jalowy, Jonas; Lee, Yong-Woo; Schehr, Grégory (arXiv:2511.09191)
We study the statistics of the number of real eigenvalues in the elliptic deformation of the real Ginibre ensemble. As the matrix dimension grows, the law of large numbers and the central limit theorem for the number of real eigenvalues are well understood, but the probabilities of rare events remain largely unexplored. Large deviation type results have been obtained only in extreme cases, when either a vanishingly small proportion of eigenvalues are real or almost all eigenvalues are real. Here, in both the strong and weak asymmetry regimes, we derive the probabilities of rare events in the moderate-to-large deviation regime, thereby providing a natural connection between the previously known regime of Gaussian fluctuations and the large deviation regime. Our results are new even for the classical real Ginibre ensemble.